Corporate social responsibility communication in social networking sites: unfinalisable and dialogical processes of legitimation - Glozer, Sarah Alice (2015)
Building upon constitutive models of corporate social responsibility (CSR) communication, which appreciate the role of both organisations and stakeholders in constructing CSR, this thesis suggests that understanding of CSR is on-going and emergent through unfinalisable legitimation processes in social networking sites (SNSs). Constructed upon management research that has examined discursive legitimation processes, this thesis shifts away from CSR communications research into websites, CSR reports and press releases, to descriptively investigate discourse within interaction (dialogue) in the textually rich SNS context. The thesis contributes to the CSR literature by challenging conventional definitions of legitimacy, which suggest that objective, legitimacy ‘realities’ are espoused from ‘transmission’ (sender-orientated) models of communication, to offer interpretations of legitimation processes rooted within discursive and dialogical constructionism.